Financial and management accounting - Sadiku, Babatunde Muhammed Tajudeen (Abuja: Damat-Mega Consult Ltd, 2020)
The book is made up of nineteen chapters of which one chapter was devoted to international Financial Reporting Standard (IFRS) while the last session comprises 300 multiple choice questions and answers.
Includes bibliographical references
ucj 07/7/2021
Loans
Keywords: Managerial accounting; Accounting; Finance management; Accounting -- Problems, exercises, etc